Thiirane linkers directed histone H2A diubiquitination suggests plasticity in 53BP1 recognition. Issue 84 (3rd October 2019) - Liang, Jun; Gong, Qingyue; Li, Ying; Zheng, Yong; Zheng, Ji-Shen; Tian, Changlin; Li, Jia-Bin
Abstract : Four diubiquitinated H2A analogues were newly synthesized and used to reveal the plasticity of ubiquitin chains in 53BP1 recognition. Abstract : Polyubiquitination with diverse linkages on histones provides another layer of accuracy and complexity for epigenetic regulation, which is rarely studied. Herein, K27 or K48-diubiquitin modified H2A analogues were chemically synthesized using thiirane linkers. These permitted in vitro binding studies suggested the plasticity of ubiquitin chains in 53BP1 recognition.